2000
DOI: 10.1116/1.1324621
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Tg and reaction rate with film thickness in photoresist: A thermal probe study

Abstract: A thermal probe technique, local thermal analysis, was used to measure the glass transition temperature (T g ) and reaction rate as a function of film thickness in chemically amplified photoresists. Using this technique, heat loss into a resist film was monitored as the temperature of the probe was ramped from ambient to temperatures as high as 200°C. The thermal events, glass transition temperature or heat evolved during reaction, were recorded as a function of the probe temperature. The T g of the photoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 21 publications
1
57
0
Order By: Relevance
“…The change in Tg as a function of film thickness is well known in the polymer literature, [8][9][10][11] and has been modeled by Keddie et al (Eqn. 1).…”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in Tg as a function of film thickness is well known in the polymer literature, [8][9][10][11] and has been modeled by Keddie et al (Eqn. 1).…”
Section: Experimental Approachmentioning
confidence: 99%
“…[28][29][30] Since Tg is known to be dependent on film thicknesses, [8][9][10][11] and Tg is closely related to acid diffusion, 31 LER degradation in thin films may be caused by an increased diffusion of acid. JSR donated two sets of resists for this study.…”
Section: Pag Attachmentmentioning
confidence: 99%
“…Acid photo-generated diffusion during the PEB or forward-scattering electrons during the e-beam exposure can explain this phenomenon [9][10][11][12]. In reality, it is very difficult to identify the real cause.…”
Section: E-beam Exposurementioning
confidence: 99%
“…8 However, their application to EUVL has significant drawbacks such as shallow penetration depth of EUV by high optical absorbance, blur of patterned images due to smaller depth of focus than PR thickness and due to back scattering of electrons at PR surface. 9 Thin polymer films with a thickness of tens of nanometers or self-assembled monolayers ͑SAMs͒ with monomolecular thickness have been suggested as a new platform to overcome these problems.…”
mentioning
confidence: 99%
“…Some research groups reported their possibility as PR and practical applications in lithography. 8,10 These monomolecular layers are formed by immersing a substrate into a solution of surface-active materials or by spin coating. To our knowledge, impurities in solution and atmosphere can cause several undesired problems such as nonuniform density, irregular orientation, and height fluctuation during the formation.…”
mentioning
confidence: 99%